Influence of Substrate-Target Distance on Structural and Optical Properties of Ga and (Al + Ga)-doped ZnO Thin Films Deposited by Radio Frequency Sputtering. (22nd September 2019) - Toma, M.; Marconi, D.; Pop, Mariana; Lung, C.; Pop, A.
Abstract: Ga-doped ZnO and (Ga + Al) co-doped ZnO thin films were deposited on glass substrates by radio frequency magnetron sputtering for three distances d between a substrate–target. The influence of the distance between substrate–target upon structure, microstructure, vibrational properties, and optical band gap of the thin films was analyzed by X-ray diffraction, atomic force microscopy (AFM), Raman spectroscopy, and optical transmission measurements. The diffraction patterns revealed that the ZnO film crystallites are preferentially oriented with the (002) planes parallel to the substrate surface. AFM images show a smooth and uniform surface as well as a high compact structure. The Raman results reveal that the co-doping with Al + Ga introduces 2B1 (low) band and leads to the increase of intensity for longitudinal-optic's band. In the visible region, the average value of the transmittance was above 80%.